Primary immunodeficiencies - Notarangelo, Luigi D. (Journal of allergy and clinical immunology, 2010)
In the last years, advances in molecular genetics and immunology have resulted in the identification of a growing number of genes causing primary immunodeficiencies (PIDs) in human subjects and a better understanding of the pathophysiology of these disorders. Characterization of the molecular mechanisms of PIDs has also facilitated the development of novel diagnostic assays based on analysis of the expression of the protein encoded by the PID-specific gene. Pilot newborn screening programs for the identification of infants with severe combined immunodeficiency have been initiated. Finally, significant advances have been made in the treatment of PIDs based on the use of subcutaneous immunoglobulins, hematopoietic cell transplantation from unrelated donors and cord blood, and gene therapy. In this review we will discuss the pathogenesis, diagnosis, and treatment of PIDs, with special attention to recent advances in the field.